THE EXCHANGE RATE OF THE RUPIAH IN INDONESIA: VOLATILITY AND ECONOMIC STABILITY - Aprilliantoni, Aprilliantoni; Jimale, Farhan Ali (Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
The exchange rate of the rupiah is inelastic, which means that changes in the exchange rate do not always lead to significant changes in the supply and demand for the currency. The objective of this research is to analyze the factors influencing the inelasticity of the rupiah exchange rate and its impact on the Indonesian economy. Using literature review and secondary data analysis methods, this study will identify factors such as inflation, monetary policy, and global economic uncertainty that contribute to the inelasticity of the rupiah exchange rate. The research methodology adopts a comprehensive literature review approach by examining the current conditions of the local currency exchange rate, key factors, and potential volatility. This study refers to a number of academic sources and central banks, including the latest academic papers. The research results show that although there is exchange rate volatility, the market's reaction to that volatility tends to be minimal, thus having a significant impact on economic stability.